Imobilização de α-amilase em blendas de pectina-pva - Cruz , Maurício Vicente (2013)
Enzymes have several characteristics in advantage to the conventional chemical catalysts. However, their use is limited by reaction conditions and, in this context, the enzyme immobilization arise improving the kinetic characteristics in the reaction environment. Natural polysaccharides are promising candidates as supports for enzyme immobilization, especially due to their biodegradability. Among the natural polysaccharides, pectin is distinguished by the ability to form gels, as well as the formation of structures for chemical-delivery systems. In this work were produced and characterized blends of polyvinyl alcohol and pectin containing the α-amylase Termamyl® immobilized by entrapment using crosslinked polymers in different glutaraldehyde concentrations (0.25, 0.5, 0.75, 1.0 and 1.25%). Part of the material was cut in pellets 6 mm in diameter and the other was crushed, followed by the measurent of the amylase activity. The effect of crosslinking agent on the activity of the immobilized enzyme and on the rate of enzyme released was tested for over 24 h. It was also evaluated the solubility of the material in water (pH 5.7) in a 0.2 mol L-1 hydrochloric acid (pH 2.0), 0.1 mol L-1 sodium phosphate buffer (pH 6.5) and ruminal buffering solution (pH 7.0). The materials were tested for their tensile strength (TS) and percentage of elongation. The blend produced in 0.5% glutaraldehyde was incubated in the presence of bovine rumen fluid for 24 h and 48 h to evaluate the mass loss and the amylase-delivery capacity. The scanning electron microscopy showed that the blends have a very irregular and rough surface. The activity of the powder pectin/PVA/amylase was higher than in the material in pellet form. The system pectin / PVA / amylase had higher solubility at pH 6.5. Testing of the tensile strength showed that the blend produced with the highest concentration of glutaraldehyde (1.25%) has greater resistance among the other, supporting a maximum load of 0.69 kgf and elongation of 24.22%. Apparently, variations in the concentration of glutaraldehyde does not have any effect on the activity of the entrapped amylase. In enzyme-delivery assays, the blend produced using 0.25% glutaraldehyde showed a higher capacity to release the enzyme with an activity of 0.07 EU after 24 h of incubation. Tests in rumen fluid demonstrated that the material has a mass loss of approximately 80% after 24 and 48 h of incubation and enzyme activity of 0.021 and 0.099 EU / mg of material after 24 and 48 h, respectively. Reactors in continuous hydrolysis of starch in the rumen cattle was observed that the blend prepared at a concentration of 1.25% showed better performance regarding the ability of continuous release of α-amylase, resulting in a considerable enzymatic activity even after 36 h of incubation. The starch remaining in the reactors was lower (0.81 mg / mL) in the reactor where it had the highest rate of hydrolysis (blend with 1.25% glutaraldehyde) and higher (2.19 mg / mL) in the reactor found that the lowest rate of hydrolysis by the action of the blends with 0.25% of the crosslinking agent.